2020
DOI: 10.1111/tbed.13757
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing chicken farmers' decisions to implement prevention and control measures to reduce avian influenza virus spread under endemic conditions

Abstract: Highly Pathogenic Avian Influenza (HPAI) H5N1 was first reported in 1959 on a small poultry farm in Scotland, UK (Capua & Alexander, 2007). Since then, several localized outbreaks occurred in different countries across the world. However, in 1996, HPAI H5N1 emerged in southern China, and subsequently spread across Asia, Europe and Africa, resulting in high mortalities of birds, and requiring the culling of many infected and unaffected flocks (Alexander, 2000; OIE, 2019a). Moreover, the zoonotic potential of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Recent studies have identified social and psychological factors that influence farmers' decisions about the implementation of biosecurity such as available information ( 9 ), farmers' knowledge and experience ( 10 13 ), social pressure ( 12 , 14 16 ) and time or economic constraints ( 13 , 16 19 ). This array of factors determines what kind of biosecurity measures farmers will adopt.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified social and psychological factors that influence farmers' decisions about the implementation of biosecurity such as available information ( 9 ), farmers' knowledge and experience ( 10 13 ), social pressure ( 12 , 14 16 ) and time or economic constraints ( 13 , 16 19 ). This array of factors determines what kind of biosecurity measures farmers will adopt.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically a low cost efficiency is observed, only 9% and 18% of traditional and modern systems, respectively, demonstrated cost efficiency, reinforcing the pressing need to distinguish between production systems due to their divergent operational requirements. This refers to the observations of Gupta et al [41] on the importance of tailoring interventions to specific farming practices.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the implementation of AI prevention and control measures is strongly influenced by farmers' perceptions about the measures to be introduced (e.g., wearing protective equipment might be considered by farmers as an impediment to effectively handling chickens) ( 62 ). In addition, limited financial resources and the actual cost of interventions might also constrain the implementation of improved biosecurity on farms ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%